Mediação cultural e políticas públicas para a cultura: uma análise sobre curadoria de exposições na Pinacoteca do Ceará - Castro, Aryadna Pereira de (2024)
This research aims to analyze aspects of cultural mediation that instrumentalize the relationship between public policies for culture, represented by the National Culture Plan (PNC) and the curatorial practice of the exhibitions held in the "Bonito pra Chover" exhibition, promoted by the Pinacoteca do Ceará. To this end, we adopted as specific objectives: a) to highlight activities applicable to the process of curating collections, in the National Plan of Cultural; b) to analyze the exhibition “Bonito pra Chover”, from the Pinacoteca do Ceará, and two exhibitions that comprise it: “No lápis da vida não tem borracha” and “Amar se aprende amando” from the curatorial aspect; c) to reflect on the relationship between the public policies put into practice from curating the researched exhibitions and the aspects of cultural mediation that are presented in this relationship. It displays as a theoretical reference an anthropological and semiotic deepening of the concept of culture and the relations of cultural mediation with Information Science, public policies aimed at culture and discussion on protective curation. Regarding the methodological procedures, the research is qualitative in nature, with an exploratory and descriptive method. To collect data, it conducts a survey and mapping of documents from the National Culture Plan and two exhibitions from “Bonito para Chover”, at the Pinacoteca do Ceará; it conducts interviews with the curators of the selected exhibitions and analyzes the data through a comparison between the documental material and the interviews. It concludes that cultural mediation is intrinsically linked to the process of curating exhibitions and to public policies for culture, constituting a dynamic environment of symbolic construction, in which those responsible for policies, professionals involved in an exhibition or a presentation, and the public are an active and an integral part of the mediation process.